Spatial distribution and service equity of sports venues in central China - Kou, Wenhai; Liu, Haoyu; Zhai, Jiahao (Frontiers in Earth Science, 2025)
As a key emerging pillar, the sports industry plays a significant role in promoting the high-quality development of regional and national economies. However, research on the spatial distribution characteristics of sports venues is insufficient, particularly when considering population size and density. This study focuses on the six provinces in central China, examining the spatial distribution features of sports venues and the balance in service population coverage. Using point of interest (POI) data for sports venues, the seventh national census data, and population density data, this study employs GIS spatial analysis methods such as mean nearest neighbor distance, kernel density estimation, and overlay analysis. The findings reveal that sports venues in the six central provinces exhibit a pattern of high-density clustering in provincial capital. The spatial distribution of sports venues is most influenced by permanent population and GDP, while showing little correlation with land area. Most of these facilities are concentrated in areas with high population densities, particularly in the capital cities. However, the current distribution of sports venues in many cities across the six provinces does not adequately meet the needs of the local population. To address this imbalance, it is recommended that the number and placement of sports facilities in the six central provinces should fully account for the distribution and density of the local population. While prioritizing development in provincial capitals, efforts should also be made to accelerate the construction of sports venues in sub-high-density core areas, especially in economically underdeveloped cities. Furthermore, the development of sports venues in towns and townships should be leveraged to promote local leisure sports and sports tourism.